PRVNÍ VÝSLEDKY TESTOVÁNÍ VLIVU INSEKTICIDŮ NA MRAVENCE [FIRST RESULTS OF TESTING THE EFFECT OF INSECTICIDES ON ANTS ] - Pavel Pech; Jakub Svoboda1; Michal Skalský; Jana Ouředníčková (Vědecké Práce Ovocnářské, 2023)
Ants are a large group of animals that also live in orchards and gardens. Their presence on fruit trees is often associated with presence of aphids, and their perception by the public is therefore rather negative. The article below describes the importance of ants in nature and their role in orchards. Furthermore, as part of this study, the first results are published with an evaluation of the effect of selected insecticides on Lasius niger queens and L. niger and Lasius brunneus workers. Laboratory experiments show that none of the tested products had a significant effect on queens or workers of L. niger within 72 hours. In contrast, increased mortality was observed in L. brunneus workers with all tested products, often even at very low concentrations. The most significant effect was observed with Sivanto Prime, when the mortality of L. brunneus workers was determined to be 53% after 24 hours of application and 70% after 72 hours.